Penerapan Arsitektur Morphosis pada Game Center Di Kota Kendari - Mukhlis Mukhlis; Ilham Ilham; Surya Baskara (Arsitektur Universitas Muhammadiyah Kendari, 2021)
One of the advances in entertainment facilities and facilitation in the city of Kendari is progress in the internet (virtual world) and in the field of games. This can be seen with the emergence of various entertainment facilities that are engaged in internet cafes (internet cafes) and games. Game Center in Kendari with the Morphosis Architecture Approach is the process of making a container or place that is centered to provide entertainment about the development of games in Kendari City with the process of forming an innovative, iconic building and friendly to the urban environment. The basic concept of Game Center planning and design in Kendari City through interior and exterior structuring with an emphasis on innovative studies iconic buildings and friendly to the urban environment as a goal of the Game Center with the concept of Morphosis Architecture. Game Center Planning in Kendari with the Morphosis Architecture approach must be used in accordance with the functions outlined in the design reference so that it can have a positive impact both for the building manager, the government, the drafting of further references and the wider community.